2017
DOI: 10.4103/ijo.ijo_157_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spectral domain optical coherence tomography parameters in ocular hypertension, preperimetric, and early glaucoma

Abstract: Purpose:The objective of this study is to evaluate the diagnostic ability of retinal nerve fiber layer (RNFL), macular, optic nerve head (ONH) parameters in healthy subjects, ocular hypertension (OHT), preperimetric glaucoma (PPG), and early glaucoma (EG) patients, to reveal factors affecting the diagnostic ability of spectral domain-optical coherence tomography (SD-OCT) parameters and risk factors for glaucoma.Methods:Three hundred and twenty-six eyes (89 healthy, 77 OHT, 94 PPG, and 66 EG eyes) were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
1
16
3
Order By: Relevance
“…The mean RNFL thickness tipping point was 89µm. In Aydogan's study, it was 90µm [25]. The maximum average RNFL thickness that was measured in our study was below all of these levels.…”
Section: Discusioncontrasting
confidence: 54%
“…The mean RNFL thickness tipping point was 89µm. In Aydogan's study, it was 90µm [25]. The maximum average RNFL thickness that was measured in our study was below all of these levels.…”
Section: Discusioncontrasting
confidence: 54%
“…First, the definition of pre-perimetric glaucoma of Triolo et al differed from others. 11,24,25 They defined preperimetric glaucoma eyes as having average and quadrant RNFL thickness within 95% and 99% confidence limits. Such a definition may cause selection bias as only "healthier" preperimetric glaucoma eyes were included.…”
Section: Discussionmentioning
confidence: 99%
“…3 Pre-perimetric glaucoma was defined as eyes having optic discs appearance suspicious of glaucoma but without evidence of repeatable glaucomatous VF damage. 11,24,25 A suspicious appearing optic disc was defined as a disc with observable excavation, neuroretinal rim narrowing or notching, or a localized or diffuse RNFL defect suggestive of glaucoma with stereophotographs. 23 RNFL thickness measurement by OCT was not considered as a criterion of pre-perimetric glaucoma.…”
Section: Participantsmentioning
confidence: 99%
“…After excluding this study, heterogeneity was largely reduced (I 2 = 34%, Supplementary Figure 12) and the funnel plot became symmetrical (Table 6 and Supplementary Figure 13, P-value of Egger's test increased from 0.195 to 0.745). In addition, the sensitivity analysis of average mGCC thickness in PPG eyes and EG eyes demonstrated that the study by Aydogan et al (39) was the major source of the heterogeneity (Table 8).…”
Section: Sensitivity Analysesmentioning
confidence: 98%
“…Several studies using OCT have reported that the attenuation of the peripapillary retinal nerve fiber layer (pRNFL), macular ganglion cell plus inner plexiform layer (GCIPL), and macular ganglion cell complex (mGCC) could be hallmark features of glaucoma ( 20 , 22 , 24 , 25 ). Although some investigations have revealed the continuum of glaucoma from mild to advanced stages, studies have shown inconsistencies regarding the diagnostic values of OCT indicators in differentiating PPG from EG ( 26 44 ) and in differentiating PPG from OHT ( 39 , 43 , 45 48 ).…”
Section: Introductionmentioning
confidence: 99%